2007
DOI: 10.1111/j.1471-0528.2007.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning from adverse clinical outcomes: major obstetric haemorrhage in Scotland, 2003–05

Abstract: Objective To describe a system for learning from cases of major obstetric haemorrhage.Design Prospective critical incident audit.Setting All consultant-led maternity units in Scotland, between 1 January 2003 and 31 December 2005.Population Women suffering from major obstetric haemorrhage (estimated blood loss ‡2500 ml or transfused ‡5 units of blood or received treatment for coagulopathy during the acute event).Methods Hospital clinical risk management teams reviewed local cases using a standard, national asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 44 publications
3
88
1
8
Order By: Relevance
“…12,16 Kodla CS et al identified a hysterectomy rate of 10.31% which was similar to findings of Drief et al 19,22 Regarding maternal outcomes, 25.6% had DIVC, 8.5% developed septicaemia and 6% developed acute renal The most common cause was placenta previa with bleeding and irreversible haemorrhagic shock.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…12,16 Kodla CS et al identified a hysterectomy rate of 10.31% which was similar to findings of Drief et al 19,22 Regarding maternal outcomes, 25.6% had DIVC, 8.5% developed septicaemia and 6% developed acute renal The most common cause was placenta previa with bleeding and irreversible haemorrhagic shock.…”
Section: Discussionsupporting
confidence: 69%
“…12 The most common cause of massive obstetric haemorrhage in our study was PPH contributing to 41.4% and uterine atony was the commonest cause of PPH. The second most common cause was placenta previa/acreta (34%) and next was abruption (13%) Kodla CS et al have also identified uterine atony as the most common cause of obstetric haemorrhage in their study.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Relevant factors are thought to be an increasing mean age of childbirth, more deliveries by Caesarean section, women with complex medical disorders choosing to become pregnant, multiple pregnancies following assisted reproduction and an increased likelihood of placenta praevia or accreta in recent years as identified by the most recent CEMACH report [20]. In addition to us, both Ryan [13] and Brace [21] report successful management of haemodynamic instability resulting from the obstetric haemorrhage in a HDU setting. We find the intra-arterial monitoring in HDU a useful tool for reasons of accuracy, reduced disturbance to mothers of frequent blood pressure readings through manual or automated cuffs and avoiding repeated venepuncture for blood sampling.…”
Section: ó 2008 the Authorsmentioning
confidence: 99%